Is Being" Smart and Well Behaved" a Recipe for Happiness in Western Australian Primary Schools? - O Rourke, J.; Cooper, Martin; Gray, C. (Canadian Center of Science and Education, 2012)
Little is known about the relationship between students’ perceptions of their behaviour and intellectual status within the classroom and their happiness. Educational practitioners consistently confront misbehaviour and academic failure; whether this is an indicator of student happiness is unclear. In this exploratory research two hundred and fifty six students were asked to self-rate their happiness via a faces scale. These students also completed a self-concept scale focussed on behavioural adjustment and intellectual and school status to determine whether these were factors that impacted on their happiness. Additionally, parents and teachers rated the participant’s happiness. The findings of this research indicate that the students’ perceptions of their behaviour and academic capability accounted for variance in their self-rated happiness. Both sub-scales accounted for more variance in the students’ self-reported happiness than the teachers’ and parents’ ratings. The findings of this research are consistent with the few previous studies that attribute social factors such as belonging to childhood happiness.